(3GdeaVd TQM GdeaUds - (3Ydj Hf eMeO Hf YHO GdUeO GdgeOGfqj GdeUQj GdSNGhj GdTGaYqj, CHh GdMSf, Yde GdOjf , J (B643 (3g`s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3CYdGe eYGQa HdaX GdJKfjI hGdLeY hPdc EfeG LGA ai GdCeGcf ef GdLHGd hGdHbGY GdJi dGjaGQb HYVgG HYVkG s
(3BNQgG (B:s
(3bGd GdTGQM bO JbOe Gdbhd hdG CMOc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1775s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3MGdI GdfSNI SjFI s
Keywords: (3GddZIs